2014
DOI: 10.1158/0008-5472.can-14-0008
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 R132H Mutation Generates a Distinct Phospholipid Metabolite Profile in Glioma

Abstract: Many patients with glioma harbor specific mutations in the isocitrate dehydrogenase gene IDH1 that associate with a relatively better prognosis. IDH1-mutated tumors produce the oncometabolite 2-hydroxyglutarate. Because IDH1 also regulates several pathways leading to lipid synthesis, we hypothesized that IDH1-mutant tumors have an altered phospholipid metabolite profile that would impinge on tumor pathobiology. To investigate this hypothesis, we performed 31 P-MRS imaging in mouse xenograft models of four huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 60 publications
5
80
0
5
Order By: Relevance
“…WT or IDH1 R132H as described earlier (29). Constructs contain a C-terminal biotin acceptor peptide and a HIS-tag, which allows distinction from endogenous IDH1…”
Section: Methodsmentioning
confidence: 99%
“…WT or IDH1 R132H as described earlier (29). Constructs contain a C-terminal biotin acceptor peptide and a HIS-tag, which allows distinction from endogenous IDH1…”
Section: Methodsmentioning
confidence: 99%
“…Distinct phospholipid metabolic profiles are seen in gliomas w i t h d e f e c t i v e I D H 1 , e x p r e s s e d a s d e c r e a s e d phosphoethanolamine and increased glycerophosphocholine (Esmaeili et al 2014). (3) Molecular testing, also modified for ICC, is available to demonstrate mutations in BRAF V600E, part of the RAS signalling pathway, in melanoma, in many diverse carcinomas and also in some brain tumours such as some gangliogliomas (Brown et al 2014;Pearlstein et al 2014;Fisher et al 2014;Bledsoe et al 2014;Dvorak et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…(2) Germ-line polymorphism is associated with isocitric dehydrogenase (IDH1) enzymatic mutations, many of which are also 1p-19q co-deletions and an R132H protein of IDH1 can be demonstrated immunocytochemically in tissue sections (Rodríguez et al 2014;Esmaeili et al 2014). Distinct phospholipid metabolic profiles are seen in gliomas w i t h d e f e c t i v e I D H 1 , e x p r e s s e d a s d e c r e a s e d phosphoethanolamine and increased glycerophosphocholine (Esmaeili et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fractional flux, which depends on the activity of pyruvate carboxylase, is therefore increased in cells with an IDH1 mutation. Morteza et al [14] demonstrated that mutated IDH1-R132H affects phosphoethanolamine and glycerophosphocholine and subsequently alters phospholipid metabolism in glioma.…”
Section: Idh Mutationmentioning
confidence: 99%